World music concise : a global journey - Miller, Terry E (Routledge, 2019)
World Music CONCISE: A Global Journey, Second Edition, introduces students to the diversity of musical expression around the world, taking them across the globe to experience cultural traditions that challenge the ear, the mind, and the spirit. Based on the Fourth Edition, this Second CONCISE Edition serves as an introduction to the many and varied world music traditions. It stays rooted in a solid pedagogical framework and maintains the text’s familiar travel theme while condensing the number of "sites" from 70 to 44. These sites are carefully selected from the existing compilation so as to remain representative of all continents and regions.